ผลการจัดการเรียนรู้พลศึกษาโดยใช้กิจกรรมพิลาทิสร่วมกับการบริหารสมองที่มีต่อผลสัมฤทธิ์ทางการเรียนและทักษะการคิดหลากหลายของนักเรียนมัธยมศึกษาตอนปลาย - ธัญญารัตน์ สีน้ำคำ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The purpose of this research was to study the effects of physical education learning management using Pilates activities with Brain Gym on learning achievement and divergent thinking skills of upper secondary school students, between the experimental group that received Pilates activities with Brain Gym and the control group receiving normal learning management. The sample included 40 students divided equally into two groups: an experimental group and a control group. The research instruments consisted of eight lesson plans, a pretest and posttest for learning achievement, and a divergent thinking skills test. The experiment was conducted over a period of 8 weeks for 1 day per week at 50 minutes per day. The tests were conducted to measure learning achievement regarding knowledge, morality, attitude, sports skills, and physical fitness along with divergent thinking skills. The data were analyzed by using mean, standard deviation, and t-test. The research findings were as follow: 1) The mean scores of the learning achievement in Physical Education and divergent thinking skills using Pilates activities with Brain Gym of the experimental group after learning were significantly higher than before learning at .05 level. 2) The mean scores of the learning achievement in Physical Education and divergent thinking skills using Pilates activities with Brain Gym of the experimental group after learning were significantly higher than the control group at .05 level.